PENYELESAIAN TINDAK PIDANA PENCURIAN DENGAN KEKERASAN YANG DILAKUKAN OLEH ANGGOTA POLRI - TITIN APRIANI (GANEC SWARA, 2018)
The purpose of this study was to find out: (a). causes of theft by violence committed by members of the national police, (b). how to resolve the crime of theft by violence committed by members of the police. This research is useful to provide knowledge in studying or applying a legal science, especially criminal procedural law, through an empirical action in the field / community. Whereas practically, the results of this study will be used as an input or contribution of thought to the relevant officials / officials to improve the quality of the implementation of duties, especially in the application of legal regulations that apply to similar cases. The results showed that the cause of police officers committed theft and violence due to two main factors, namely internal factors and temporary external factors, the process or method of solving criminal cases committed by members of the National Police, ie there was no difference between the community members but also members of the National Police adjudicated by the police code of ethics.